Classical tradition in Luis Alberto de Cuenca’s Cuaderno de vacaciones (Minerva, 2017)
This paper examines the classical influences in Luis Alberto de Cuenca’s Cuaderno de vacaciones (Holiday notebook) (2014). References to Greek and Roman mythology, literature, and philosophy, both explicit and implicit, are abundant, and are almost always recreated from a personal and modern perspective. Furthermore, the classical tradition is crucial at the formal level, as the poet, following the model of Callimachus, updates the Hellenistic epigram with his verses. Thus, the classical world brought closer to the world of today's readers.
Keywords: Classical Tradition; Cuaderno de vacaciones (Holiday notebook); Luis Alberto de Cuenca; epigram